2012
DOI: 10.1177/0883073812439345
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Pediatric Palliative Care Service Utilization in Children With a Progressive Neuromuscular Disease Who Died on a Palliative Care Program

Abstract: Recent studies and consensus statements have expressed the need to involve palliative care services in the care of children with progressive neuromuscular diseases (PMD), yet there have been no reviews of the utilization of palliative care services by children who died on a palliative care program. We conducted a retrospective chart review of all children who had a PMD who died on a single-center palliative care program. Twenty cases were identified. Services utilized by these patients included respite care, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 18 publications
(22 reference statements)
1
21
0
Order By: Relevance
“…Results from this study are supported by the literature in a number of ways, including the plethora of medications given to these children 3 16 17. One of the most striking findings is the children's large symptom experience.…”
Section: Discussionsupporting
confidence: 74%
“…Results from this study are supported by the literature in a number of ways, including the plethora of medications given to these children 3 16 17. One of the most striking findings is the children's large symptom experience.…”
Section: Discussionsupporting
confidence: 74%
“…31 Prominent symptoms in the last 24 hours of life include respiratory distress, pain, nausea, vomiting, and anxiety. 32 One study found that children who die of advanced Vol. 166, No.…”
Section: Symptoms At End Of Lifementioning
confidence: 99%
“…24,25 Despite the increasing prominence of PPC programs in US hospitals, however, information on the numberand scope of these programs is sparse, with the most recent study of program prevalence now 7 years old, and this limited to Children' s Oncology Group institutions. [26][27][28][29] In contrast, the proliferation of adult palliative care programs has been tracked more closely, demonstrating that over the past decade the number of adult programs has more than doubled (although availability varies from state to state). [30][31][32] More detailed characterizations of adult palliative care have also been published.…”
mentioning
confidence: 99%